Bridging the implementation gap for climate mitigation in ASEAN: a comprehensive capacity-building framework - Emi Minghui Gui; Indra Overland; Beni Suryadi; Zulfikar Yurnaidi (Fulbright Review of Economics and Policy)
Purpose – The paper systematically examines the capacity building needs of energy and climate stakeholders in the Association of Southeast Asian Nations (ASEAN). It looks at conditions and opportunities for improvements in institutional, organisational, technological, innovation and financing capacities. This paper provides a guide to concrete capacity building programs and implementations to accelerate the implementation of National Determined Contributions (NDCs) and low-carbon energy transition in the ASEAN region. Design/methodology/approach – This paper proposes a comprehensive capacity-building framework, drawing on transition management theory and the interactive systems framework for capacity building. The assessment is based on interviews with representatives of the ministry responsible for energy policy and the ministry responsible for climate policy in each ASEAN country, as well as a survey among a broader set of Southeast Asian energy and climate experts from academia, think tanks and international development partners. Findings – The paper identifies the priority areas for capacity building for each ASEAN country and the region as a whole. Each country has a unique set of needs and priorities. At the regional level, the widest capacity gaps were observed in institutional capacity, technical capacity, human resources capacity, financing capacity and the capacity to develop policy and legislation. Specific gaps for capacity building are discussed in delivering strategic areas of energy transition, such as electrification of transportation, development of the green supply chain, deploying renewable energy, energy efficiency, strengthening finance and investment and reducing dependencies on fossil fuels. Originality/value – This paper helps fill the gap for detailed capacity needs analysis and facilitates long-term plans/strategies and their implementation. The insights help to increase ASEAN energy and climate stakeholders’ understanding of the interaction between energy and climate, therefore enhanced capability in developing more effective action maps and intervention points in achieving NDCs and sustainable development goals.